Soil properties of sugarcane fields controlling triazine leaching potential. - Portocarrero, Rocio; Aparicio, Virginia Carolina; De Geronimo, Eduardo; Costa, Jose Luis (CSIRO PUBLISHING, 2019)
Atrazine and ametryn are pre- and post-emergence herbicides widely used in sugarcane fields. Both herbicides are characterized by their moderate to high mobility in soil and are regarded as a threat to hydrologic systems. Physical and chemical soil properties are highlighted as one of the factors governing the fate of pesticides in hydrologic systems. The aim of our study was to estimate the leaching potential of atrazine and ametryn in soils of the saline alluvial plain of Tucumán cultivated with sugarcane crop. Miscible displacement experiments were carried out in triplicate using undisturbed topsoil cores from four farm fields. Field 1 was in plant, fields 2 and 3 were in second ratoon, and field 4 was in third ratoon. Experimental breakthrough curves were fitted to the convection-dispersion equation; results showed that hydraulic transport was in equilibrium conditions, meaning that all the soil water was involved in solute convective transport. Atrazine had asymmetric breakthrough curves, revealing chemical non-equilibrium conditions, with at least two sorption-desorption sites participating in the process. In contrast, ametryn concentrations in leached samples were low and inconsistent; therefore, no breakthrough curves could be described. Total recoveries reached 10% and 2% for leached atrazine and ametryn, respectively, of the total applied. For an estimated annual recharge of 100 mm, these leached amounts would exceed the international reference values for drinking water.